2021
DOI: 10.4187/respcare.08622
|View full text |Cite
|
Sign up to set email alerts
|

High Failure Rate of Noninvasive Oxygenation Strategies in Critically Ill Subjects With Acute Hypoxemic Respiratory Failure Due to COVID-19

Abstract: BACKGROUND: The efficacy of noninvasive oxygenation strategies (NIOS) in treating COVID-19 disease is unknown. We conducted a prospective observational study to assess the rate of NIOS failure in subjects treated in the ICU for hypoxemic respiratory failure due to COVID-19. METHODS: Patients receiving first-line treatment NIOS for hypoxemic respiratory failure due to COVID-19 in the ICU of a university hospital were included in this study; laboratory data were collected upon arrival, and 28-d outcome was recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 44 publications
(58 reference statements)
2
48
0
6
Order By: Relevance
“…Presence of moderate-to-severe dyspnea might be a marker of disease severity correlated to outcomes, possibly configuring a clinical sub-phenotype of COVID-19 severe respiratory failure. Use of noninvasive support in COVID-19 patients is common [9][10][11][12]. While considering a trial of noninvasive respiratory support in COVID-19 patients with moderate-to-severe respiratory failure, the presence of dyspnea, measured during conventional oxygen therapy, in conjunction with other variables such as respiratory rate and degree of hypoxia may represent a simple alert tool to identify patients with the highest risk of endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of moderate-to-severe dyspnea might be a marker of disease severity correlated to outcomes, possibly configuring a clinical sub-phenotype of COVID-19 severe respiratory failure. Use of noninvasive support in COVID-19 patients is common [9][10][11][12]. While considering a trial of noninvasive respiratory support in COVID-19 patients with moderate-to-severe respiratory failure, the presence of dyspnea, measured during conventional oxygen therapy, in conjunction with other variables such as respiratory rate and degree of hypoxia may represent a simple alert tool to identify patients with the highest risk of endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…The current evidence demonstrates HFNC is safe and reduces the need for intubation in COVID-19 without clear mortality benefit [ [37] , [38] , [39] , [40] , [41] , [42] , [43] ]. However, high failure rates have been observed with NIPPV and HFNC in COVID-19, with one study finding 61% of patients required endotracheal intubation [ 44 ]; close monitoring for signs of failure is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with coronavirus disease 2019 (COVID-19) pneumonia can develop severe hypoxemia and require PEEP, although these patients are at greater risk of NIV failure than patients with ARF with other aetiologies [ 28 ]. Some authors have suggested that helmets might reduce aerosol spread [ 29 , 30 ], as confirmed by some exploratory studies [ 31 , 32 ].…”
Section: Use Of Helmets To Deliver Cpapmentioning
confidence: 99%